Tối ưu hóa điều kiện tổng hợp HMX - Thanh, Đỗ Xuân; Hữu, Chu Chiến; Giao, Ngô Văn (Vietnam Journal of Chemistry, 2015)
This paper presents the optimization results of synthesis conditions of 1,3,5,7-tetranitro-1,3,5,7-tetraazacyclooctane (HMX) according to modified Bachmann method. The ranges of variables were: hexamine (0.29-0.43 mol), nitric acid 99.5 % (1.67-2.13 mol), ammonium nitrate (1.20-1.52 mol), paraformaldehyde (0.04-0.10 mol) and acetic anhydride (3.16-3.52 mol). The constant parameters were: temperature (44±2) oC, reaction time (1st and 2nd dosing-time: 30 minutes, 1st aging-time: ≤ 5 minutes, and 2nd aging-time: 60 minutes) and acetic acid 388 ml. The optimum conditions for maximum yield of HMX (57.27 %) were hexamine 0.35 mol; nitric acid 99.5 % 2.03 mol; ammonium nitrate 1.35 mol; paraformaldehyde 0.10 mol and acetic anhydrite 3.44 mol.